Problems experienced by professional nurses providing care for HIV/AIDS patients in public hospitals at Polokwane Municipality, Limpopo Province, South Africa - Mametja, V. L.; Lekhuleni, N. E; Kgole, J. C. (My University, 2013)
The purpose of this study was to describe the problems experienced by professional nurses providing health care to patients living with HIV and AIDS in the public hospitals of Polokwane municipality, Limpopo province. A qualitative descriptive, contextual and phenomenology design was used to described the problems experienced by professional nurses. The target population included all professional nurses providing care to HIV positive patients in medical units in public hospitals of Polokwane municipality. Purposive sampling was used to select professional nurses until data saturation was reached after 11 professional nurses were interviewed. An audiotape was used with the permission of professional nurses to capture their responses during the semi-structured interviews. The nurses reported feelings of frustrations, treatment delay, lack of knowledge on HIV and AIDS, lack of support systems and work overload as challenges faced in caring for HIV/AIDS patients. The need for in-service education for professional nurses on treatment of HIV positive patients was discussed and recommended.
Published in; African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) March 2013 (Supplement 1), pp. 48-61
Keywords: HIV positive patients; AIDS; Professional nurses; Public hospitals; AIDS (Disease) -- South Africa